Effect of Prolonged Dehumidification on the Chemical Properties of Crassiacarpa and Mangium Honey - Fadhallah, Esa Ghanim; Nawansih, Otik; Nurainy, Fibra; Mubarik, Depri (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Honey is a natural substance bees produce from nectar, flower sap, or liquid collected from living plant parts. The honey undergoes bee modification and binding before being stored in hexagonal combs. Effective dehumidification is crucial for enhancing honey quality and extending its shelf life. This study aimed to evaluate the effects of prolonged dehumidification time, honey type, and their interaction on the quality of Crassiacarpa and Mangium honey and to determine the optimal dehumidification treatment to meet the SNI 8664-2018 standard. A factorial Completely Randomized Design (CRD) with three replications was employed. Two liters each of Crassiacarpa and Mangium honey were placed in trays with a thickness of ±2 cm and dehumidified at 25°C and 40% humidity for 24, 48, 72, and 96 hours. Following dehumidification, the honey was analyzed for moisture content, total acidity, pH, and sensory attributes (taste, color, aroma, texture). Data were analyzed descriptively. The results demonstrated that dehumidification time significantly impacted moisture content, total acidity, and pH. Honey type significantly affected moisture content and pH. The interaction between dehumidification time and honey type significantly affected pH. The optimal treatment for both honey types was dehumidification for 96 hours, which resulted in honey that met the SNI 8664-2018 standard.